2020
DOI: 10.1111/jeb.13632
|View full text |Cite
|
Sign up to set email alerts
|

Male phenotypes in a female framework: Evidence for degeneration in sperm produced by male snails from asexual lineages

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 60 publications
3
21
0
Order By: Relevance
“…Evolutionary decay of mating-related traits in asexual contexts is a plausible explanation for these results and is consistent with a previous study demonstrating evidence for decay of sperm traits in the male offspring occasionally produced by asexual female P. antipodarum [15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Evolutionary decay of mating-related traits in asexual contexts is a plausible explanation for these results and is consistent with a previous study demonstrating evidence for decay of sperm traits in the male offspring occasionally produced by asexual female P. antipodarum [15].…”
Section: Discussionsupporting
confidence: 92%
“…Evolutionary decay of mating-related traits in asexual contexts is a plausible explanation for these results and is consistent with a previous study demonstrating evidence for decay of sperm traits in the male offspring occasionally produced by asexual female P. antipodarum [15]. Despite absence of evidence for discriminatory mating behaviour, asexual females mated at a nearly identical frequency with P. antipodarum males as sexual females (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…At one extreme, the pairing of JU1373 hermaphrodites from Réunion with JU1630 males from Cape Verde yielded no cross-progeny from 22 trials, while at the other extreme, Hawaiian QG131 hermaphrodites and South American NIC58 males yielded cross-progeny in each of 34 trials. Male crossing probability was much more variable than that of hermaphrodites, consistent with relaxed selection (residual deviance of 179.2 vs. 85.2, null deviance 232.6, binomial linear model) ( Cutter, 2019 ; Jalinsky et al, 2020 ; Noble et al, 2015 ; Palopoli et al, 2008 ; van der Kooi and Schwander, 2014 ). Same-strain pairings were indistinguishable from inter-strain pairings (p=0.88, likelihood ratio test [LRT] of binomial linear models).…”
Section: Resultsmentioning
confidence: 56%
“…Among the focal Peromyscus species within our study, we found more variation in the sperm head aspect ratio and head width across than within species, with some species producing sperm with a relatively wider head (P. eremicus, P. polionotus, and P. maniculatus) and others producing a more elongated head (P. californicus, P. leucopus, and P. gossypinus). The elongation of the sperm head, driven by the compactness of the nucleus within [59][60][61][62][63][64] is expected to reduce hydrodynamic drag and promote more efficient, faster movements [16, but see 15]. Sperm head shape has been observed in both inter-and intra-species analyses across taxonomic groups [17][18][19][21][22][23], but see 65,66].…”
Section: Discussionmentioning
confidence: 99%